2014
DOI: 10.3892/ol.2014.1897
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SDF-1 and CXCR4 transcript variants and CXCR7 in epithelial ovarian cancer

Abstract: Chemokine stromal cell-derived factor-1 (SDF-1) and its receptors, CXCR4 and CXCR7, have been implicated in epithelial ovarian cancer progression and metastasis. However, limited data are available on the expression levels of SDF-1 and CXCR4 variants and CXCR7 in human epithelial ovarian cancer. The present study aimed to characterize the expression pattern and levels of SDF-1, CXCR4 and CXCR7 in normal human ovaries and epithelial ovarian cancer. The expression of SDF-1 and CXCR4 transcript variants and CXCR7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…No changes in CXCR4 and CXCR7 expression level are observed. Elevated plasma SDF-1α level in epithelial ovarian cancer patients is not associated with the presence of tumors and/or metastases, however reflects a general response to the disease [72].…”
Section: Introductionmentioning
confidence: 99%
“…No changes in CXCR4 and CXCR7 expression level are observed. Elevated plasma SDF-1α level in epithelial ovarian cancer patients is not associated with the presence of tumors and/or metastases, however reflects a general response to the disease [72].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the expression of CXCL12, CXCR4, and CXCR7 in Figure 6 The role of CXCL12 and its receptors CXCR4, CXCR7 on Apoptosis of KGN cells. Apoptosis rate of KGN cells after 100 ng/mL rhCXCL12 (CXCL12, n = 6), 100 ng/mL rhCXCL12 with 1 μg/mL CXCR4 antagonist AMD3100 (CXCL12 + AMD3100, n = 6), 100 ng/mL rhCXCL12 with 10 μg/mL anti-CXCR7 neutralizing antibody (CXCL12 + Anti-CXCR7, n = 6), 100 ng/mL rhCXCL12 with 10 μg/mL isotype IgG (CXCL12 + IgG, n = 6) incubation for 24 h. *P < 0.05. human epithelial ovarian cancer has been examined (Jaszczynska-Nowinka et al 2014). Meanwhile, the joint expression of CXCL12 and its receptors CXCR4 and CXCR7 in the ovary of PCOS rat is shown for the first time in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…The SDF-1 concentration gradient is a driving force for stem cell migration [41]. Studies showed that the expression of SDF-1 was present at extremely low levels or even not originally identi ed in normal ovaries [43,44]. However, after injury, the chemokine SDF-1 level increased in tissue, which is critical for the chemotaxis of stem cells homing to the injured or ischemic tissue [24,27,[45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%